Gentamicin Vestibulotoxicity: Further Insights From a Large Clinical Series. Issue 7 (August 2020) - Fu, Terence S.; Carr, Simon D.; Douglas-Jones, Paul; Dillon, Wanda; Ilan, Ophir; Syed, Iqbal Mohammed; Leis, Jerome; Gold, Wayne; Pothier, David D.; Rutka, John A.
Abstract : Objective: To review insights gained from a 21-year experience with gentamicin-induced vestibulotoxicity including differences in vestibulotoxicity between single daily dosing (SDD) and multiple daily dosing (MDD) regimens. Study Design: Retrospective case series. Setting: Tertiary care center. Patients: Patients with gentamicin vestibulotoxicity referred to the Hertz Multidisciplinary Neurotology Clinic between January 1993 and September 2014. Intervention: None. Main Outcome Measures: Spectrum of vestibular dysfunction measured using videonystagmography, vestibular evoked myogenic potentials, video head impulse testing, and magnetic scleral search coil testing. Results: Of 53 patients with gentamicin-induced vestibulotoxicity, 24 received SDD and 29 received MDD treatment. The most common indications for treatment were sepsis, endocarditis, and osteomyelitis. Angular acceleration receptor function (semicircular canals) was more commonly affected than linear acceleration receptor function (otolithic organ of the saccule; 100% vs. 62%). A significant proportion of patients (53%) developed vestibulotoxicity in the absence of nephrotoxicity and 40% experienced vestibulotoxicity in a delayed fashion up to 10 days posttreatment cessation (mean 3.9 ± 0.7). Therapeutic monitoring did not necessarily prevent delayed vestibulotoxicity. Nephrotoxicity was less common for SDD compared with MDD (60% vs. 35%, p = 0.01). However, the SDD group experienced vestibulotoxicity at a lower cumulative dose (6.3 vs. 7.0 g, p = 0.04) and shorter duration of therapy (20.7 vs 29.4 d, p = 0.02). Conclusions: Our study further highlights important insights regarding gentamicin-induced vestibulotoxicity. While SDD is associated with decreased risk for nephrotoxicity compared with MDD, it confers a higher risk for vestibulotoxicity. Abstract : Supplemental Digital Content is available in the text